2016
DOI: 10.1021/jacs.6b03338
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Photo-catalytically Active Surface of SrTiO3

Abstract: A major goal of energy research is to use visible light to cleave water directly, without an applied voltage, into hydrogen and oxygen. Since the initial reports of the ultraviolet (UV) activity of TiO 2 and SrTiO 3 in the 1970's, researchers have pursued a fundamental understanding of the mechanistic and molecular-level phenomena involved in photo-catalysis. [1][2][3][4][5][6][7] Although it requires UV light, after four decades SrTiO 3 is still the gold standard for splitting water. It is chemically stable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 42 publications
(83 reference statements)
2
48
0
Order By: Relevance
“…Surface pKa prediction based on bond valence analysis suggests that water exchange will influence the proton transfer reactions underlying the acid/base reactivity at the interface. Our findings provide important new insights for understanding complex interfacial chemical processes at metal oxide-water interfaces.The interfaces between metal oxides and water are among the most important in nature and in emerging energy applications, with wide ranging impacts from photocatalytic water splitting [1][2][3][4] to the geochemical cycling of elements 5,6 . Key chemical processes such as adsorption, electron transfer, growth, and dissolution all depend principally on the atomic structure adopted at these interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface pKa prediction based on bond valence analysis suggests that water exchange will influence the proton transfer reactions underlying the acid/base reactivity at the interface. Our findings provide important new insights for understanding complex interfacial chemical processes at metal oxide-water interfaces.The interfaces between metal oxides and water are among the most important in nature and in emerging energy applications, with wide ranging impacts from photocatalytic water splitting [1][2][3][4] to the geochemical cycling of elements 5,6 . Key chemical processes such as adsorption, electron transfer, growth, and dissolution all depend principally on the atomic structure adopted at these interfaces.…”
mentioning
confidence: 99%
“…For example, dissolution and solute adsorption are regulated by the structure of interfacial water 7,8 . Surface acid/base chemistry 9,10 arises from the types and arrangement of terminal metal-coordinating aquo/hydroxyl groups 3,[11][12][13] .…”
mentioning
confidence: 99%
“…Through surface-sensitive characterization and electronic-structure calculation, it has been shown that SrTiO 3 can undergo a TiO 2 -rich surface reconstruction [7][8][9][10][11][12]. This result has been further confirmed by the detailed comparison of computationally predicted structures with accurate x-ray reflectivity data [9,13].…”
Section: Introductionmentioning
confidence: 90%
“…Previously reported terminations include the single-TiO 2 layer [9,12,35], and the stoichiometric double-TiO 2 terminated interface in the (1×1) and (2×1) surface unit cells (2 ML (1×1) and 2 ML (2×1)) [7,9,10,12]. In addition, a unique type of SrTiO 3 surface structure induced under electrochemical conditions has been recently reported by Plaza and coworkers [13]. Specifically, the SrTiO 3 interface has been shown to undergo a substantial reconstruction upon "training" at positive bias, forming a non-stoichiometric, triple-TiO 2 terminated interface, which exhibits significantly improved activities in alkaline solutions.…”
Section: B Surface Structure Of Slab Modelsmentioning
confidence: 99%
“…Strontium titanate (SrTiO 3 ) as a functional metal oxide material has attracted extensive research interests due to novel structures and properties exhibited at its surfaces . It is a paradigmatic substrate for epitaxial growth of photocatalyst, high‐ T c superconductors, ferroelectrics . Moreover, the existence of two‐dimensional (2D) electron gas and liquid on the surface and interface of SrTiO 3 makes it an appealing substitute for conventional semiconductors .…”
Section: Introductionmentioning
confidence: 99%